Prevalence and risk factors for Extended-Spectrum Beta-Lactamase-producing- Enterobacteriaceae in French military and civilian travelers: A cross-sectional analysis. Issue 23 (May 2018) - Flateau, Clara; Duron-Martinaud, Sandrine; Haus-Cheymol, Rachel; Bousquet, Aurore; Delaune, Déborah; Ficko, Cécile; Merens, Audrey; Rapp, Christophe
Abstract: Background: International travel is a risk factor for colonization with Extended-Spectrum Beta-Lactamase-producing- Enterobacteriaceae (ESBL-E). We describe the prevalence of and risk-factors for ESBL-E colonization in civilian and military travelers. Methods: Patients hospitalized in the infectious diseases department of Bégin Military Hospital (France) from May 2012 to November 2015, who had traveled abroad over the past two months, were screened for intestinal colonization with ESBL-E. Results: Forty-one out of 166 travelers (24.7%) had ESBL-E colonization, predominantly Escherichia coli. The risk factors for ESBL-E colonization in the univariate analysis were a treatment with any antibiotic in the last two months (OR 4.19, 95% CI 1.91–9.16) or with a beta-lactam in the same period (OR 3.35, 95% CI 1.44–7.82), and an hospitalization in the last two months (OR 3.96, 95% CI 1.91–9.16). The military status, military mission or military accommodation were not associated with an increased risk of ESBL-E colonization. In the multivariate analysis, a treatment with any antibiotic in the last two months was significantly associated with ESBL-E colonization (OR 6.71, 95% CI 3.36–19.08). Conclusion: Antibiotic treatment in the two previous months is strongly predictive of ESBL-E colonization in international travelers, while the military status and its specific living conditions are not.